A New Obstacle Avoidance Method for Service Robots in Indoor Environments - Budiharto, Widodo; Santoso, Ari; Purwanto, Djoko; Jazidie, Achmad (Journal of Engineering and Technological Sciences, 2012)
The objective of this paper is to propose an obstacle avoidance method for  service  robots  in  indoor  environments  using  vision  and  ultrasonic  sensors. For  this research,  the  service  robot  was  programmed  to  deliver  a  drinking  cup from a specified starting point to the recognized customer. We have developed three main modules: one for face recognition, one for obstacle detection, and one for avoidance maneuvering. The obstacle avoidance system is based on an edg edetection  method  using  information  from  the  landmark  and  planned-path generation. Speed, direction and distance of the moving obstacle are measured using  vision  and  distance  sensors  in  order  for  the robot  to  make  an avoidance maneuver. Algorithms for obstacle avoidance are proposed and a new geometric model is introduced for making good avoidance maneuvers. The main aim of this research is to provide a complete mechanism for obstacle avoidance by vision based service robots, where common obstacle avoidance methods, such as PVM, do  not  provide  such  a  feature.  We  present the results  of  an  experiment  with  a service  robot  in  which  the  proposed  method  was  implemented,  after  which  its performance is evaluated.